Constitutional Judicial System: A Comparison between Indonesia and France - Munazih, Muflih; Faramida, Dina (TRUNOJOYO LAW REVIEW, 2025)
This study aims to compare the Constitutional Court of Indonesia (Mahkamah Konstitusi Republik Indonesia or MKRI) and the French Constitutional Council (Conseil Constitutionnel) in terms of their historical foundations, legal authority, structural composition, and judicial review mechanisms. The objective is to assess their effectiveness in upholding constitutional governance and propose adaptive models for better protection of fundamental rights. The research method employs a normative juridical approach, incorporating statutory, conceptual, and analytical perspectives. It analyzes primary and secondary legal materials, including constitutions, statutory laws, court decisions, and doctrinal writings. The study focuses on positive legal norms and compares the implementation of judicial review practices in both legal systems using a qualitative analysis framework. The study reveals key differences in the scope and timing of constitutional review: Indonesia employs a posteriori review, which permits legal correction after enactment, while France utilises a priori review to prevent unconstitutional laws before promulgation, later supplemented by the Question Prioritaire de Constitutionnalité (QPC) for limited a posteriori review. Structurally, the Indonesian Court is a judicial organ, while the French Council functions more as a political-legal oversight body. The novelty lies in proposing a hybrid model that incorporates both a priori and a posteriori mechanisms to strengthen constitutional protection, particularly for Indonesia, by recommending the integration of preventive review authority within its existing system.